The real thing imitation and authenticity in American culture, 1880-1940 - Orvell, Miles 1944- (University of North Carolina Press, 2014)
In this classic study of the relationship between technology and culture, Miles Orvell demonstrates that the roots of contemporary popular culture reach back to the Victorian era, when mechanical replications of familiar objects reigned supreme and realism dominated artistic representation. Reacting against this genteel culture of imitation, a number of artists and intellectuals at the turn of the century were inspired by the machine to create more authentic works of art that were themselves "real things." The resulting tension between a culture of imitation and a culture of authenticity, argues Orvell, has become a defining category in our culture. The twenty-fifth anniversary edition includes a new preface by the author, looking back on the late twentieth century and assessing tensions between imitation and authenticity in the context of our digital age. Considering material culture, photography, and literature, the book touches on influential figures such as writers Walt Whitman, Henry James, John Dos Passos, and James Agee; photographers Alfred Stieglitz, Walker Evans, and Margaret Bourke-White; and architect-designers Gustav Stickley and Frank Lloyd Wright